PENGARUH METODE READ ALOUD BERBANTUAN BUKU RAMAH CERNA TERHADAP KETERAMPILAN MEMBACA PERMULAAN KELAS II SDN BAHAGIA 06 - Suci Mareta Dwi Saputri; Hafizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the read aloud learning method assisted by user-friendly books on the early reading skills of second-grade students at SDN Bahagia 06. This research employed a quantitative approach with a quasi-experimental design using a pretest-posttest group design. The study involved 62 students divided into two groups: the experimental class and the control class. The instrument used was the EGRA test, assessed based on five aspects: letter recognition, syllable reading, reading non-meaningful words, reading meaningful words, and reading comprehension. The data analysis results showed that the average posttest scores of the experimental class were higher than those of the control class. The t- test indicated a significance value of 0.000 (<0.05), meaning that there is a significant effect of the read aloud method assisted by user-friendly books on early reading skills. Thus, the implementation of the read aloud method supported by user-friendly books is effective in improving students' early reading skills in an active and enjoyable manner.